DUAL NATURE OF WORK OF A ART: FORMULA AND FORM - Daujotytė-Pakerienė, Viktorija (Literatūra, 2013)
The article deals with the dual nature of a work of art, which is perceived as a relations of formula and form. There is a reference to H. Focillon’s conception of the forms of soul as the base of relation between art and author. Examples from Lithuanian art and humanistics are mentioned. There is a focus on the beginning of the seventies of the twentieth century when the article’s problem was of greater relevance. At the same time and in the same publication, both the Lithuanian philologist professor Donatas Sauka and the famous mathematician academician Vytautas Statulevičius shared similar ideas when striving for harmony between a formula and an alive form. Onė Baliukonytė, a young poet at that time, raised the relation between the intuitive and the intellectual aspects as a problem. There was an emphasis on the idea which is also relevant today – the intensity of the inner form protects writings from formulas and their mechanical interception. Arvydas Šliogeris, a representative of technologies and formulas, as a humanistic author marks a radical separation between formula and form.